-49=17t-10t

Simple and best practice solution for -49=17t-10t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -49=17t-10t equation:


Simplifying
-49 = 17t + -10t

Combine like terms: 17t + -10t = 7t
-49 = 7t

Solving
-49 = 7t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-7t' to each side of the equation.
-49 + -7t = 7t + -7t

Combine like terms: 7t + -7t = 0
-49 + -7t = 0

Add '49' to each side of the equation.
-49 + 49 + -7t = 0 + 49

Combine like terms: -49 + 49 = 0
0 + -7t = 0 + 49
-7t = 0 + 49

Combine like terms: 0 + 49 = 49
-7t = 49

Divide each side by '-7'.
t = -7

Simplifying
t = -7

See similar equations:

| (y-2)=-4x+4 | | -5=8(x-4)-5x | | (-3a)(2a)(-4a)= | | x+8=x^2+4x-7 | | 8v+2(v+2)=-36 | | -5+13=5b-8-4b | | c=.5mv | | c=1/2mv | | -4=6x+2(-4x) | | 2.5x+6y=480 | | 5n^2-2n+28=0 | | -b=4a+3c-p | | X^5-3x+2x=0 | | 2xy-5=9 | | y=5+-10x | | -10x=-12 | | 13x+29y=-23 | | 20m-7-2m=8m-2 | | 2.3m+1=1.3m+7 | | -2-2=4-2X+3X | | 1/2*x-5=10 | | Y=-3/8x-2 | | 7.34=2(3.14)r | | e^8x+3=19 | | 15*500= | | 43x+2=38 | | 4w+2-3w=7 | | -4(x-4)=-3(x-7)-4 | | 5+10-5*2+45+2x=400 | | 40X+(1.5X)(5)=661 | | 8p-19=-28+7p | | 15+4a^2=2a^3-5 |

Equations solver categories